Clinical importance of cross‐sectional area of intercostal muscles in patients with chronic obstructive pulmonary disease. (25th January 2017) - Ju, Sunmi; Lee, Seung Jun; Park, Mi Jung; Cho, Yu Ji; Jeong, Yi Yeong; Jeon, Kyung Nyeo; Bae, Kyungsoo; Lee, Jong Deog; Kim, Ho Cheol
Abstract: Introduction: Limb muscle wasting is one of main systemic manifestation of chronic obstructive pulmonary disease (COPD). However, the change of respiratory muscle is unclear. Objectives: This study assessed the cross‐sectional area (CSA) of the intercostal muscles (ICMs) in patients with COPD, using chest computed tomography (CT) and determined its association with the clinical characteristics of COPD. Methods: They retrospectively reviewed 60 patients with stable COPD and compared them with 30 controls. CSA (mm 2 ) of the ICM on chest CT was measured at the midline level of the lateral arch of the bilateral first rib with a 3‐mm slice thickness by using CT histogram software. The association with the clinical characteristics of COPD and with the control groups was assessed. Results: CSA of the ICM and the CSA/body mass index (BMI) were lower in the COPD group than in the control group. Patients with Global Initiative for Chronic Obstructive Lung Disease (GOLD) stage 4 had a significantly lower CSA of the ICM than patients with stage 1, 2, and 3. CSA of the ICM was positively associated with FEV1, %FEV1 predicted, FEV1 /FVC ratio, and BMI and negatively associated with age. However, there were no associations with PaO2, PaCO2, smoking status, 6‐minute walk test, frequency of acute exacerbation of COPD, and serum C‐reactive protein level. Conclusion: Intercostal muscle atrophy occurs in COPD patients and is associated with severity of airway obstruction, BMI, and increasing age.